Valuation of the company Gerresheimer Horsovsky Tyn spol. s r.o. - Velebová, Štěpánka; Hnilica, Jiří, 1976-; Sieber, Martina; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2012)
The goal of this master thesis is to appraise the medical plastic systems producer Gerresheimer Horsovsky Tyn spol. s r.o. as of July 1, 2012 with the purpose of selling the company to an unknown buyer. The thesis is divided into theoretical and practical part. In the theoretical part there are defined all the important theoretical aspects and methods for business valuation used in this thesis. In the second, practical, part theory is applied to the particular company. Firstly, the appraised company is introduced followed by its strategic and financial analysis, value generators, and financial plan. The core valuation methods used are the two phase discounted cash flows method and the comparable companies method. At the end, the estimated business value is discussed.
Vedoucí práce: Jiří Hnilica
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses